MENGURAI ISTIḤSĀN SEBAGAI SUMBER HUKUM ISLAM - Bintarawati, Fenny; Rosyid, Maskur (Institut PTIQ Jakarta, 2020)
Istiḥsān, although its use as a legal argument is disputed, it has proven relevant to be applied in the contemporary era. Through literature study, observation, and interviews, this paper finds that istiḥsān with its various qarinahs can be used as reason for determining the law of a case. Istiḥsān bi al-maṣlaḥah is applied as a method in establishing the law of permissibility to use corpses as research material to ensure a greater benefit for life. Meanwhile istiḥsān bi al-ḍarūrah is applied as a method of establishing the permissibility law using the corpse because it is the only means that can be used.